E-COMMERCE SYSTEM FOR “TOKO MIRING” HOMEWARE STORE - Wisnu Pratama Hardomo; Sandi Darmowinoto (President University, 2022)
“Toko Miring” is a growing company sellinghousehold appliances, where the promotion and sales processis still conventional. This means that the customer has to go tothe Italic Shop to be able to purchase the product. Thedevelopment of an e-commerce sales system at the TokoMiring store is a step to increase sales and product promotionso that it can provide benefits for the company. The purposeof building an e-commerce system for selling this product isthat customers can place orders for products without havingto come to the Miring Shop, the company can also solve theproblem of product processing, order processing so that it canmake it easier for consumers to get information aboutproducts from the Miring Store. This system was createdusing PHP and MySQL as the program. The result of makingthis project is an e-commerce system for Toko Miring whichcan be used as a means of sales promotion that can beaccessed anywhere and anytime, the buying process can alsotake place without having to come to the store.